Armanesia Blockchain System: Blockchain and IFPS-Based Archive System Prototype - Asmiyanto, Taufik; Putrawan, Nafi; Widiarta, Yusuf; Inamullah, Hanif; Zaidan Abdurrahman Qois (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
Document integrity is critical to public trust in archives management. Armanesia is an innovative research project aims to develop prototype of information systems to support the management of digital archives based on blockchain technology. The project uses blockchain technology to record verification, immutability, and other metadata derived from various types of digital records. In this system, archives are permanently stored through peer-to-peer distribution and consensus verification without the need for a third party. The continuum archive cycle is based on Armanesia workflow infrastructure. The prototype is built through open-source technologies such as IPFS (Interplanetary File System) for blockchain-enabled file systems to design a system prototype using the SDLC (System Development Life Cycle) method. Armanesia technology can be applied for both public and private blockchain ecosystems.